Health Expenditures and the Effectiveness of Covid-19 Prevention in International Comparison - Jaqueline Hansen; Antonia Reinecke; Hans-Jörg Schmerer (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In the beginning of the COVID-19 pandemic, governments had to rely on Non-Pharmaceutical Interventions in their struggle against the spread of the virus. The stringency of the lockdowns differed across space and time as governments had to adjust their strategy dynamically to the country-specific development of the crisis. We examine the effectiveness of lockdowns with a focus on the role of health care based upon both the between and the within-variation of our panel-data. The within-variation over time allows us to control for unobserved heterogeneity through fixed-effects. The results reveal that lockdowns had significant effects on the mortality rates associated with COVID-19. Marginal effects are estimated conditional on the state of the health care system before the crisis. Lockdowns were more efficient in countries with well-supported health care systems. Marginal effects turn insignificant when per capita health expenditure dips below the mean. We can show that both results are driven by economic development. Per capita GDP is highly correlated with public health expenditure but it is not a perfect substitute.
Keywords: I10; I13; I14; 330; Covid-19; health expenditures; lockdown